The Influence of Internal Locus of Control, Disiplin Preventif, and Work Ethic on Performance of Civil Servants Dindikpora - Aulicha, Irni Ulul; Subroto, Setyowati; Wiyanti, Sari (Universitas Pamulang, 2026)
This research focuses to analyze the influence of Internal Locus of Control, Preventive Discipline, and Work Ethic on the Performance of Civil Servants (ASN) at the Brebes Regency Education, Youth, and Sports Office. The main issues raised in this study are the fluctuations in employee performance and the level of tardiness, which remain serious concerns. This study uses a quantitative approach with a population of 58 civil servants working at the Brebes Regency Education, Youth, and Sports Office. The sample was determined using saturated sampling technique, so that all members of the population became research respondents. Data collection was conducted through the distribution of questionnaires, then analyzed using multiple linear regression with the help of SPSS. The results showed that Internal Locus of Control had a positive and significant effect on employee performance with a regression coefficient of 0.123 and a significance of 0.010. Preventive Discipline had a positive and significant effect on employee performance with a regression coefficient of 0.053 and a significance of 0.021. Work Ethic also has a positive and significant effect on employee performance with a regression coefficient value of 0.161 and a significance of 0.000. Simultaneously, the three independent variables have a significant effect on employee performance with a calculated F value of 19.899 and a significance of 0.000. The coefficient of determination (R²) value of 0.525 indicates that 52.5% of employee performance variation can be explained by Internal Locus of Control, Preventive Discipline, and Work Ethic, while the remaining 47.5% is influenced by other factors outside the research model.